Eficacia biologica de Clomazone en el control de malezas en amaranto (Amaranthus hypochondriacus L.) - Alavez-Ceron, G.=700 1 Barrales-Dominguez, J.S.; Bolaños-Espinoza, A.
(En, Es)
Ilus., 9 ref
Keywords: AMARANTHUS HYPOCHONDRIACUS; ESCARDA; MALEZAS; HERBICIDAS; CLOMAZONE; FITOTOXICIDAD; MEXICO; REVISTA CHAPINGO